2015
DOI: 10.3109/00207454.2015.1080699
|View full text |Cite
|
Sign up to set email alerts
|

The study of sleep disorder factors in patients with Guillain–Barré syndrome

Abstract: In this study, we explore the sleep disorders and its associated factors in patients with Guillain-Barré syndrome (GBS), so as to work out appropriate interventions to promote early recovery of the patients. This study subjects included 49 patients with GBS who had been admitted to the Department of Neurology at The Affiliated Hospital of Hebei University, fulfilling National Institute of Neurological and Communicative Diseases and Stroke (NINCDS) criteria for GBS; 37 cases were male and 12 female (age: 27-68 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…Regarding the sleep assessment, the study showed EDS in initial evaluation of GBS patients as evidenced by shortened mean latencies of MSLT. This result agrees with that of Gao et al ( 2016 ) who found EDS in GBS patients through using the Pittsburgh Sleep Quality Index. Polysomnographic assessment during this stage showed marked prolongation of WASO on the expense of reduction in TST, decreased SE, and increased SSTI.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding the sleep assessment, the study showed EDS in initial evaluation of GBS patients as evidenced by shortened mean latencies of MSLT. This result agrees with that of Gao et al ( 2016 ) who found EDS in GBS patients through using the Pittsburgh Sleep Quality Index. Polysomnographic assessment during this stage showed marked prolongation of WASO on the expense of reduction in TST, decreased SE, and increased SSTI.…”
Section: Discussionsupporting
confidence: 93%
“…These results agree with that of Chokroverty ( 2003 ) who stated that chest wall and respiratory muscle fatigue with extension of the REM sleep hypotonia to affect the respiratory muscles (the extra-ocular and respiratory muscles are normally not involved in the REM sleep hypotonia) may be the cause of OSA in GBS patients. Periodic limb movement index also showed significant increase in early disease stages, and this result is also passing with the work of Gao et al ( 2016 ).…”
Section: Discussionsupporting
confidence: 88%
“…However, in addition to sensorimotor phenomenon, sleep disturbances are also frequent in GBS patients. In hospitalized GBS patients, sleep disturbances are found in at least 50%, likely multifactorial with contributions from pain, psychiatric sequela, immobility, medication effects, and treatments/procedures [141][142][143]. Detailed sleep descriptions are often lacking, but a few studies and case reports have discussed sleep disturbances in GBS in detail.…”
Section: Guillain-barré Syndrome (Gbs Also Known As Acute Inflammator...mentioning
confidence: 99%
“…Two case studies reported that psychiatric symptoms preceded onset of physical disability, including stress, depression, anxiety and amnesia [16,17]. Table 2 includes 24 studies, including a total of 6,984 patients, that collectively reported that GBS causes psychiatric symptoms, including stress, anxiety, depression, fatigue, sleep abnormalities, visual hallucinations, paranoid delusions, disorientation, terror, and psychosis [11,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Two studies concluded that close relatives of GBS patients also experience problems of daily living and social dysfunction and have psychological needs requiring consideration and support [23,37].…”
Section: Reviewmentioning
confidence: 99%
“…The cause of residual fatigue is unknown. However, fatigue is exacerbated by sleep disturbance, which occurs in approximately 50% of patients and it is also associated with depression [27,35].…”
Section: Residual Fatigue In Gbs Patientsmentioning
confidence: 99%